2002
DOI: 10.1128/aem.68.3.1232-1239.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of XYL3 ( d -Xylulokinase) from Pichia stipitis and Characterization of Its Physiological Function

Abstract: XYL3, which encodes a D-xylulokinase (EC 2.7.1.17), was isolated from Pichia stipitis CBS 6054 genomic DNA by using primers designed against conserved motifs. Disruption of XYL3 eliminated D-xylulokinase activity, but D-ribulokinase activity was still present. Southern analysis of P. stipitis genomic DNA with XYL3 as a probe confirmed the disruption and did not reveal additional related genes. Disruption of XYL3 stopped ethanol production from xylose, but the resulting mutant still assimilated xylose slowly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 50 publications
2
42
3
Order By: Relevance
“…The alignment results were also edited using the Jalview 2.8 tool (49) for enhanced visual presentation. To find the metabolic enzymes responsible for the xylose and cellobiose degradation, we used the XYL1, XYL2, and XYL3 proteins of P. stipitis (50,51) as well as BGLs of A. niger (BGL1; Q30BH9) (52), A. fumigatus (BTGE; B0Y9Q9) (53), and Candida wickerhamii (BGLA; Q12602) (54) as the templates. We further applied the PSORTII tool (55) to predict the cellular localization of the BLASTPsearched putative BGL genes of Y. lipolytica.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…The alignment results were also edited using the Jalview 2.8 tool (49) for enhanced visual presentation. To find the metabolic enzymes responsible for the xylose and cellobiose degradation, we used the XYL1, XYL2, and XYL3 proteins of P. stipitis (50,51) as well as BGLs of A. niger (BGL1; Q30BH9) (52), A. fumigatus (BTGE; B0Y9Q9) (53), and Candida wickerhamii (BGLA; Q12602) (54) as the templates. We further applied the PSORTII tool (55) to predict the cellular localization of the BLASTPsearched putative BGL genes of Y. lipolytica.…”
Section: Strains and Plasmidsmentioning
confidence: 99%
“…It was reported that XYL1 overexpressing S. cerevisiae mutant, produced xylitol in sequential or continuous batches [189]. Later, Jan and his collages (2003) reported that proportional increasing XYL2 expression to XYL1, potentially decreased xylitol levels [172]. They thought that the xylitol production by engineered S. cerevisiae strains resulted from an excess of NADPH relatively to NADH for the early assimilation step of xylose [80].…”
Section: Xylitol Productionmentioning
confidence: 99%
“…Later, XK from P. stipites (PsXK) has been overexpressed in an engineered S. cerevisiae background for high expression levels of XYL1 and XYL2 [171,172]. The specificity of P. stipites XK enzyme for D-xylulose was much higher, with less D-ribulose activity than the XK from S. cerevisiae [168].…”
Section: Xylulokinasementioning
confidence: 99%
See 2 more Smart Citations